Cultural Narratives and Their Impact on Family Mental Health - Bilač, Sanja; Öztop, Fehmi; Kutuk, Yasin; Karadag, Mehmet (Journal of Psychosociological Research in Family and Culture, 2024)
Objective: Cultural narratives significantly influence mental health perceptions, stigmatization, and coping mechanisms within families. This study aimed to explore the impact of cultural narratives on family mental health, identifying the key themes and categories that emerge from these narratives and their implications for mental health practice and policy.Methods and Materials: A qualitative research design was employed, utilizing semi-structured interviews with 23 participants from diverse cultural backgrounds. Theoretical saturation was achieved, ensuring a comprehensive understanding of the participants' experiences. Thematic analysis was conducted to identify main themes and categories, focusing on the nuances of cultural narratives and their impact on family mental health.Findings: Four main themes were identified: Cultural Identity and Mental Health, Family Dynamics, Coping Mechanisms, and Societal Influence. Within these themes, categories such as Cultural Stigma, Cultural Support Systems, Communication Patterns, Parenting Styles, Individual and Family Coping Strategies, and Access to Mental Health Services highlighted the complex interplay between culture and mental health. Key concepts emerged, including the role of shame and silence, community solidarity, acculturation stress, inter-generational trauma, and the importance of social support networks in navigating mental health within a cultural context.Conclusion: The study underscores the profound impact of cultural narratives on family mental health, revealing both barriers and supports influenced by cultural identity, family dynamics, societal factors, and coping mechanisms. It highlights the need for culturally sensitive mental health services and policies that recognize and address the diverse cultural narratives influencing mental health perceptions and practices.